2020
DOI: 10.1039/d0nr03969a
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of mechanical stability in the novel coronavirus spike protein

Abstract: Unveiling the nanomechanical stability of the novel coronavirus (SARS-CoV-2) spike protein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 35 publications
7
53
0
Order By: Relevance
“…The entry of viruses into mammalian cells, or "virus internalization", is a key mechanism of enveloped virus infection and is based on dynamic conformational changes of their surface glycoproteins, namely, as mediated by disulfide bond reduction and regulated by cell surface oxydoreductases and proteases [5,[8][9][10][11]. SARS-CoV-2 entry into host cells has been shown to start with destabilization of the spike protein through allosteric mechanical transition, which induces a conformational change from the closed "down" state to open "up" state of the receptor binding domain (RBD) of the spike protein [12,13]. The conformational changes of RBD and virus binding are induced by TMPRSS2 or Cathepsin L, which trigger the transition from the pre-fusion to post-fusion state [5,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The entry of viruses into mammalian cells, or "virus internalization", is a key mechanism of enveloped virus infection and is based on dynamic conformational changes of their surface glycoproteins, namely, as mediated by disulfide bond reduction and regulated by cell surface oxydoreductases and proteases [5,[8][9][10][11]. SARS-CoV-2 entry into host cells has been shown to start with destabilization of the spike protein through allosteric mechanical transition, which induces a conformational change from the closed "down" state to open "up" state of the receptor binding domain (RBD) of the spike protein [12,13]. The conformational changes of RBD and virus binding are induced by TMPRSS2 or Cathepsin L, which trigger the transition from the pre-fusion to post-fusion state [5,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 entry into host cells has been shown to start with destabilization of the spike protein through allosteric mechanical transition, which induces a conformational change from the closed "down" state to open "up" state of the receptor binding domain (RBD) of the spike protein [12,13]. The conformational changes of RBD and virus binding are induced by TMPRSS2 or Cathepsin L, which trigger the transition from the pre-fusion to post-fusion state [5,12,13]. The energy liberated by disulfide bond reduction increases protein flexibility, which is maximal when the reduced state is complete [8], thus allowing the fusion of host-virus membranes, which is otherwise impossible due to the repulsive hydration forces present before reduction [5].…”
Section: Introductionmentioning
confidence: 99%
“…An elegant experiment using the cryoelectron microscopy (cryo-EM) revealed that the change from D614 to G614 eliminates the requirements of side-chain hydrogen bond, increasing mainchain flexibility and altering interactions, and modulates glycosylation enhancing the cell entry, infectivity, transmissibility, stability of virions and high viral loads in the airways (Sheffield COVID-19 Genomics Group, 2020;Wrapp et al, 2020). Besides these differences, a new feature is the high nanomechanical stability of the SARS-CoV-2 S-ACE2 interaction compared to SARS-CoV-1 (Moreira et al, 2020). Moreira et al (2020) revealed that high mechanical stability in the SARS-CoV-2 S-ACE2 has several biological implications such as cell recognition, viral attachment, fusion and entry.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these differences, a new feature is the high nanomechanical stability of the SARS-CoV-2 S-ACE2 interaction compared to SARS-CoV-1 (Moreira et al, 2020). Moreira et al (2020) revealed that high mechanical stability in the SARS-CoV-2 S-ACE2 has several biological implications such as cell recognition, viral attachment, fusion and entry. Thus, mechanical stability might play a role in the increasing spread of COVID-19 (Moreira et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation